Fazer a ponte para a escola de todos(as) - Rosa, Cláudia Sueli Rodrigues Santa (2008)
The purpose of this study is to understand what are the matrix elements in which everyday activities of social author/authors, actor/actors and actress/actresses are embedded, in order to carry out the Escola da Ponte s political and pedagogic process (PPP). Thus, the object of this study is to reflect on an experience developed in a public school supported by the Portuguese State within the scenario of institutions that are committed to building up a school of the people by investing in democratization and community participation in their management process. The methodological course of action was targeted at the presuppositions of qualitative research (WOODS, 1999; BURGESS, 1997; MILLS, 1982; OLIVEIRA, 1998; BOGDAN and BIKLEN, 1994; MACEDO, 2000; CASAL, 1996; GEERTZ, 2000), with data collected from random word association (MACHADO and CARVALHO, 2003), the discourse of the interviewed (KAUFMANN, 1996; SILVA, 2006; 2002), observation notes and documents (ELIAS, 1997). Based on a multiple reference and theoretical framework, the investigation revealed elements that are construed as the raw material and pillars supporting the bridge of a school of the people, as well as the self-organization of the school community which emerges as a dimension that binds together all the elements and brings new arrangements into the school dynamics by moving from the individual to the society (DUPUY, 1990). Along this line, the central argument is that in the short and long run the public school quality does not spring from macro educational policies, nor from ephemeral mass-production programs, projects or governmental policies, but from the intent of the professionals working there in becoming authors and characters in the process of building up and carrying out the PPP. The Project has been conceived in the light of the needs and intentionality of the community whose support comes from the participation and social control held by the students families and the community s power to force to action public administration central agencies aiming at having the State fulfill its responsibilities